2019
DOI: 10.1002/jia2.25332
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories of emotional problems and unmet mental health needs among people newly diagnosed with HIV in China

Abstract: Introduction Concern over mental health morbidity affecting people living with HIV is increasing worldwide. The objective of this study was to describe the longitudinal trajectories of depression and anxiety, and mental health service utilization among people newly diagnosed with HIV. Methods This was an observational cohort study that enrolled people newly diagnosed with HIV consecutively and followed them for one year in Changsha, China. Socio‐demographic, clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The mortality rate from suicide is 1%, with suicide mortality rates declining post ART initiation [ 54 ]. Anxiety disorders, particularly generalized anxiety disorder (GAD), are also commonly comorbid conditions in PLWH, with 25–33% experiencing clinically significant anxiety [ 47 , 57 , 63 ]. Internalized stigma has a significant indirect effect on anxiety through self-blame [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate from suicide is 1%, with suicide mortality rates declining post ART initiation [ 54 ]. Anxiety disorders, particularly generalized anxiety disorder (GAD), are also commonly comorbid conditions in PLWH, with 25–33% experiencing clinically significant anxiety [ 47 , 57 , 63 ]. Internalized stigma has a significant indirect effect on anxiety through self-blame [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, HIV-positive course of illness varied across different participants, and those with longer illness courses may have a higher probability of experiencing SI or SA. Although there is some conflicting evidence, as previous studies reported that PLWH with longer courses coped with stress better than those with shorter courses (40).…”
Section: Discussionmentioning
confidence: 95%
“…A systematic review has shown that the median prevalence of depression and anxiety among HIV-positive individuals are 60.64% and 43.13% in China, respectively [40]. Unfortunately, poor sustainability and fragmented care of mental health care remains largely an unresolved issue in China [24]. According to the Gelberg-Andersen Behavioral Model for vulnerable populations, the HIV-related stigma might be an important factor associated with the mental health care utilization [41].…”
Section: Discussionmentioning
confidence: 99%
“…The data reported in this study derives from a longitudinal study focusing on the mental health among newly diagnosed people living with HIV. A detailed description of study design is available elsewhere [24]. Briefly, participants were consecutively recruited from the Changsha Center for Disease Control and Prevention (CDC) from March 1, 2013, to August 30, 2014.…”
Section: Participantsmentioning
confidence: 99%